Predictive value of bone turnover markers and thyroid indicators for bone metabolism in GD patients after treatment - Su, Mengxue; Chai, Jinyan; Zheng, Wei; Jia, Qiang; Tan, Jian; He, Yajing; Zhang, Ruiguo; Men, Jianlong; Liu, Wei; Shi, Tao; Ren, Jing; Dong, Liyan; et al. (Frontiers in Endocrinology, 2024)
To investigate the relationship between bone turnover markers (BTMs) and thyroid indicators in Graves' disease (GD) and to further assess predictive value of changes in early stage retrospectively.We studied 435 patients with GD and 113 healthy physical examiners retrospectively and followed up these two groups of patients after 6 months. We investigated the correlations between BTMs and other 15 observed factors, and analyzed the predictive value of FT3 and FT4 before and after treatment (FT3-P/ FT3-A, FT4-P/ FT4-A) on whether BTMs recoveried.The levels of thyroid hormones and BTMs in GD group were significantly higher than those in control group (P < 0.05) and decreased after 6 months of treatment. FT3, W, Ca and ALP were independent factors in predicting the elevation of OST. Duration of disease, FT3, TSH and ALP were independent factors in predicting the elevation of P1NP. Age, duration of disease, TRAb and ALP were independent factors in predicting the elevation of CTX-1. The AUC of FT3-P/ FT3-A and FT4-P/ FT4-A for predicting OST recovery were 0.748 and 0.705 (P < 0.05), respectively, and the cut-off values were 0.51 and 0.595. There was no predictive value for P1NP and CTX-1 recovery (P > 0.05).